Establishing reproductive seasons for the conservation of the critically endangered Kashmir red deer Cervus Hanglu - Tanushree Srivastava; Javaid Hameed; Vinod Kumar; Harika Segu; Sneha Narayan; Moomin John; Karthikeyan Vasudevan; Govindhaswamy Umapathy (Scientific Reports)
Abstract Ungulates living in seasonal environments adopt complex life history strategies to cope with pronounced temporal and spatial variability in environmental conditions and resource availability. Understanding the reproductive strategies of slow-breeding mountain ungulates and the associated stress, particularly in the context of human- and climate-induced changes, is crucial to devising effective long-term management and conservation strategies. We investigated the patterns in reproductive seasonality and stress in hangul in Kashmir Himalaya, India. We used fecal metabolites of estradiol (FEMs), progesterone (FPMs), testosterone (FAMs), and glucocorticoids (FGMs) to discern reproductive stages and stress levels. We showed that female hangul exhibited dispersed mating and birth patterns, while males experienced a more synchronized rutting season from October to December. Elevated FPM levels in females from January to March suggested pregnancies, with low levels in April indicating parturition. Both females and males exhibited a mating-related rise in FGM levels (interpreted as stress hereafter). Females also showed parturition-related stress in April and May. The spike in stress levels of both sexes in May is probably due to the disturbances from migratory livestock herders’ movements which needs further investigation. The study generates a baseline for captive breeding programs in the future. It suggests minimizing the anthropogenic disturbances during the times of mating and parturition, both being critical for the population growth of this critically endangered species.